Endospores of Bacillus subtilis with probiotic potential in animals of zootechnical interest - Milián, Grethel; Rondón, Ana J.; Rodríguez, Marlén; Beruvides, A.; Pérez, M. L. (Cuban Journal of Agricultural Science, 2022)
At present, poultry, pig and cattle production constitute the most important branches of animal production in the world, which currently contributes to fulfill the protein needs of the world population. The use of probiotics, prebiotics and synbiotics is predicted with the purpose of using them as animal growth promoters. Among the species that are most used for the elaboration of these products, are those from Bacillus genus. One of them is Bacillus subtilis, a bacterium able to stimulate the immune system, produce enzymes, resist acid pH gastric barriers, and produce antimicrobial substances that inhibit different pathogenic microorganisms. For these reasons, zootechnical additives, made with Bacillus, are considered an alternative in the current livestock industry. The objective of this review was to show the probiotic potential in pig farming, poultry farming and calf rearing that Bacillus subtilis endospores have. Key words: alternatives in animal production, calves, chickens, pigs